Transient Inhomogeneous Ionic Solutions -The Influence of the Magnetic Field Gradient - Butcher, Tim Alexander (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Solutions of paramagnetic ions and their response to magnetic field gradients of permanent magnets were studied. Paramagnetic fluids confined by solid walls only develop internal flows in a magnetic field gradient when a non-uniform concentration of the paramagnetic species is present. The simplest inhomogeneous system comprises two miscible liquids, which start off sharply separated and slowly mix by diffusion. The method of neutron imaging was adopted to map the concentration evolution of diffusing paramagnetic Gd(NO3)3 solutions. Magnetic manipulation of the paramagnetic liquid within a miscible non-magnetic liquid such as D2O is possible by modifying the condition for hydrostatic stability. A magnetic field gradient can capture a concentration of paramagnetic fluid in an ephemeral, purely magnetogravitational phenomenon that is eventually wiped out by diffusion. The addition of nonmagnetic Y(NO3)3 salt to the D2O can give rise to double-diffusive phenomena such as salt fingering instabilities which significantly hasten the mixing of the liquids by multicomponent convection. It was shown that a magnetic field gradient may serve to prevent and halt such instabilities involving Gd(NO3)3 solutions by stabilising the paramagnetic fluid. Concentration gradients in paramagnetic salt solutions can be triggered by electrosorption in porous carbon electrodes. The process of capacitive deionisation was investigated in cells containing paramagnetic Gd3+ ions by dynamic neutron imaging. Both carbon aerogels and microporous activated carbon cloths were employed as capacitive deionisation electrodes. The uptake and depletion of Gd3+ in the porous electrodes were monitored in situ. A magnetic field gradient was able to modify the concentration distribution in the ensuing inhomogeneous solution after the desalination process. The possibility of electrochemically separating rare earth ions with the assistance of a magnetic field gradient was explored. The electrolysis of a mixture of Gd(NO3)3 and Y(NO3)3 solutions under a magnetic field gradient was analysed. Rare earth hydroxides were precipitated electrochemically and captured by a Nd-Fe-B permanent magnet. Although the deposits on the working electrode followed the magnetic field profile, the method failed to separate the different rare earth hydroxides. No preference of the paramagnetic hydroxide for the regions of highest magnetic field gradient was detected.
APPROVED
Keywords: Paramagnetic Salt Solutions; Neutron Imaging; Magnetic Forces; Rare Earth Ions; Magnetoelectrochemistry; Capacitive Deionisation; Porous Carbon Electrodes